THE FLOW AND MASS TRANSFER CHARACTERISTICS OF CONCENTRIC GAS-LIQUID FLOW IN AN ADVANCED STATIC MIXER - MENG, HUIBO; LI, ZHONGGEN; YU, YANFANG; HAN, MENGQI; SONG, SHUNING; JIANG, XIUHUI; WANG, ZONGYONG; WU, JIANHUA (Chemical Industry & Chemical Engineering Quarterly, 2021)
The fluid dynamic and mass transfer characteristics of concentric upward gas-liquid flow were studied in an industrial static mixer with four equally spaced helical inserts (FKSM). The numerical simulations of the gas volume fraction in a Kenics mixer was in good agreement with the numerical and experimental results provided by Rabha et al. The characteristics of radial gas void fraction and local mass transfer coefficients in the FKSM were evaluated under different operating conditions. The velocity profiles of the concentric air phase accelerated by the bubble forces first became sharp and narrow until z/l = -3.27 and then slowly decreased and stabilized at z/l = -1.5 before entering the first mixing element. Some extra unimodal profile of radial gas holdup gradually generated near the rectangle cross-sections of the mixing elements. The αG gradually enlarged from r/R = 0.2 to r/R = 0.55 and then weakened from r/R = 0.65 to r/R = 0.874. The air void fractions in the bulk flow region decreased with the increasing initial uniform bubble diameter. The inlet effect of the first leading edge enhanced the air phase dispersion and local mass transfer coefficients sharply increased from 2.04 to 3.69 times of that in the inlet. The local mass transfer coefficients in each mixing group had unimodal profiles.